PROJECT MANAGEMENT DURING INFODEMIC OF THE COVID-19 PANDEMIC - Sergey Bushuyev; Denis Bushuiev; Victoriia Bushuieva (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of this article is the transformation of project management systems, programs and project portfolios in the context of the interaction of the infodemic and pandemic in the COVID-19 environment. Infodemiс, ahead of the pandemic, is filled with rumours, conjectures and speculation at the first stage, creating an atmosphere of fear and panic. At the same time, Agile methodologies, systems of knowledge and competencies of project and program managers come to the fore in project management. The basis of the changes lies in changing the decision-making paradigm in the management of projects and programs in the "infodemiс - pandemic" system. The goal is to study the models of interaction and mutual influence of the pandemic (infodemiс) information support during the development of the COVID-19 pandemic for the application of modern methodologies of flexible methodologies in managing projects and programs at all levels of the state and society. The key challenges to a successful project and program management are Agile Transformation. Today there is an intuitive transition to the use of flexible project and program management methodologies, which does not bring the expected results. The research results allowed the authors to build a model of interaction "infodemiс - pandemic). This model can be used to analyse the mutual influence of the information envelope in each country on the distribution of the coronavirus and project management to minimize the negative consequences of the pandemic. Conclusions: This article explores the phenomenon of "infodemiс" that occurs during the global crisis of the COVID-19 pandemic. It is proposed to apply the Agile transformation of the project management system and pandemic programs, taking into account the influence of informational "noise" in the mental space of global society. The model can significantly improve project preparation by transforming Agile management with a focus on stakeholder value systems. At the same time, it is important to use the opportunities to accelerate and increase the effectiveness of project implementation using Agile umbrella tools such as Kanban, P2M, Kaizen and others. Disinformation, which includes false claims about a "cure", conspiracy theory and misleading information about the spread of the virus will expand. The effectiveness of the response to control this "infodemiс" is likely to vary from country to country and will depend on public confidence in the authorities. New developments, including the detection of outbreaks of the virus in almost all countries of the world, the publication of epidemiological data and the start of clinical trials of the vaccine, are likely to lead to new misinformation, which will hamper efforts to control the pandemic.